Nutritional Influence on Epigenetic Marks and Effect on Livestock Production - Murdoch, Brenda M.; Murdoch, Gordon K.; Greenwood, Sabrina; McKay, Stephanie (Frontiers in Genetics, 2016)
Nutrition represents one of the greatest environmental determinants of an individual’s health. While nutrient quantity and quality impart direct effects, the interaction of nutrition with genetic and epigenetic modifications is often overlooked despite being shown to influence biological variation in mammals. Dissecting complex traits, such as those that are diet or nutrition related, to determine the genetic and epigenetic contributions towards a phenotype can be a formidable process. Epigenetic modifications add another layer of complexity as they do not change the DNA sequence itself but can affect transcription and are important mediators of gene expression and ensuing phenotypic variation. Altered carbohydrate metabolism and rates of fat and protein deposition resulting from diet-induced hypo- or hyper-methylation highlight the capability of nutritional epigenetics to influence livestock commodity quality and quantity. This interaction can yield either products tailored to consumer preference, such as marbling in meat cuts, or potentially increasing productivity and yield both in terms of carcass yield and/or offspring performance. Understanding how these and other desirable phenotypes result from epigenetic mechanisms will facilitate their inducible potential in livestock systems. Here, we discuss the establishment of the epigenome, examples of nutritional mediated alterations of epigenetics and epigenetic effects on livestock production.